P095 Association between tissue oncostatin M expression and infliximab response in corticosteroid refractory acute severe ulcerative colitis. (25th January 2019) - O'Connell, J; McDonagh, P; Clarke, N; Buckley, A; Dunne, C; Hartery, K; Larkin, J; MacCarthy, F; McCormack, P; McKiernan, S; Mehigan, B; Muldoon, C; et al.
Abstract: Background: Infliximab (IFX) is a rescue therapy for corticosteroid refractory acute severe ulcerative colitis (ASUC). A significant proportion of ASUC patients fail to respond to IFX or require accelerated dosing. Oncostatin M (OSM) is a member of the gp130 cytokine family this includes IL-6, LIF, IL-11, Cardiotrophin -1. It is receptor is a member of JAK STAT pathway. It is expressed in macrophages, monocytes, T cells and dendritic cells and is a marker on inflammation. High pre-treatment expression of the cytokine oncostatinM (OSM) has been associated with anti-TNF therapy failure. We aimed to evaluate whether OSM had utility as a tissue biomarker of IFX response in a cohort of patients with ASUC. Methods: A colonic formalin-fixed paraffin-embedded (FFPE) specimen from a patient who had colectomy for ASUC was used to optimise anti-OSM antibody for immunohistochemistry and determine staining pattern is severely inflamed tissue in patients refractory to IFX treatment. Patients attending St James's Hospital with ASUC who received rescue IFX for IV corticosteroid refractory disease were selected for inclusion. Included patients had an endoscopic assessment prior to IFX initiation. Colonic tissue slides from biopsies collected during this procedure were retrieved. Immunohistochemistry for OSM was performed on these FFPE slides and scoring performed to quantify epithelial and stromal immunostaining by two blinded investigators. The association between OSM immunostaining and colectomy and requirement for accelerated IFX dosing was assessed. p-values <0.05 were considered significant Results: In total, 21 patients were included [median age 38.3 years (21.1–28.8), median endoscopic Mayo score 3(2–3). Median follow-up 47.2 weeks (0.6–117.1). Sixty-five per cent received standard IFX induction. 7/21 (33%) required colectomy. There was no association between epithelial or stromal OSM staining and requirement for colectomy or accelerated dosing( p > 0.6 for all comparisons). Neither epithelial nor stromal OSM staining were associated with time to colectomy, p = 0.99 and 0.44, respectively. Conclusions: Tissue OSM expression was not associated with IFX response or requirement for accelerated IFX dosing in a small cohort of corticosteroid refractory ASUC patients. Further studies are required to definitively assess the utility of this biomarker in ASUC.